To the Pole: the diary and notebook of Richard E. Byrd, 1925-1927 - Byrd, Richard Evelyn, 1888-1957; Goerler, Raimund E. (Raimund Erhard), 1948- (The Ohio State University Press, 1998)
(print) 161 p. : ill. 24 cm Introduction 1 -- The Making Of An Explorer : Richard Evelyn Byrd, 1888-1924 7 -- The Greenland Expedition Of 1925 17 -- The North Pole Flight Of 1926 41 -- The Transatlantic Flight Of 1927 97 -- Epilogue : Richard Evelyn Byrd, 1928-1957 119 -- Appendix A : Chronology Of Byrd's Life 133 -- Appendix B : Navigational Report Of Byrd's Flight To The North Pole, 1926 139 -- Additional Readings 159